Direct Payment System in Sugarcane Industry: Beneficial or Unfavourable Solution? - Wahyu Rizki Harwoto; Mohammad Rondhi; Rokhani Rokhani; Anik Suwandari (Economics Development Analysis Journal, 2022)
Smallholder Farmer (PR) dominate the sugarcane supply for national sugar production. That indicates sugar production depends on the sustainability of sugarcane’s supply from smallholder sugarcane farming. 34.4 percent of sugarcane farmers in Indonesia partner with sugarcane factories, while others decide to manage independent farming. So far, the partnership is defined by the Profit-sharing system (SBH). The number of independent farmers raises why farmers decide independent farming rather than partnership. Otherwise, government through 593/TI.050/E/7/2019 propose a policy for sugarcane factories to obtain sugarcane with Direct System. This situation raises the pros and cons at the farmer's level to decide it. A direct Payment System (SPT) is a buy-sell transaction within farmers without sustainability. One of the sugar factories performing SBH partnership is PG Kebon Agung, located in Malang with a vast production capacity. This study aimed to describe the partnership and transaction mechanism, determine the decision-making factors of farmers participating in SBH partnerships, and compare the incomes. The analytical method is descriptive-qualitative, logistic regression analysis, and comparative income analysis. The results showed that SBH has advantages in assisting farmers but has weaknesses in payment times. This is the opposite of SPT, which provides faster payment times. The amount of SBH farming income is also more significant than SPT. So this study suggests that SBH farmers are suitable for farmers who have a shortage of capital. At the same time, SPT is suitable for farmers with more capital who need a faster cash flow.